Territorial Self-Government as a Conflict Management Tool - Walsh, Dawn (Federalism and Internal Conflicts, 2018)
This book provides an in-depth narrative of the difficulties facing Territorial Self-Government institutions across Northern Ireland, Bosnia, the former Yugoslav Republic of Macedonia, Moldova, and Iraq. It brings together analyses of both prominent and lesser known cases to provide a broad overview of how Territorial Self-Government operates as a conflict management tool in different contexts. Drawing on lessons from these five cases, the author demonstrates the importance of designing and implementing international guarantees to self-government and the associated difficulties. Domestic capacity development must be encouraged and international actors needs to balance the guarantees aimed at providing stability with their wider security and economic concerns. The volume also strongly connects to broader research and theory on conflict management, particularly the role of institutional design and international assistance.